Realism and regionalism : 1860-1910 - Lathbury, Roger (New York, NY : Facts On File, 2006)
"Explores the social, cultural, and historical contexts of American literature from 1860 to 1910"--P. [4] of cover.
Sectionalism, industrialism, and literary regionalism -- Slave narratives and race relations -- Mark Twain (1835-1910) -- Urban writers and internationalism : Alger, Howells, James, Wharton -- Regionalism -- Naturalism, determinism, and social reform : Crane, Norris, London, DuBois, Sinclair, Dreiser -- Timeline.
Includes bibliographical references (p. 94) and index.
Keywords: American literature -- 19th century -- History and criticism; Realism in literature; American literature -- 20th century -- History and criticism; Regionalism in literature